The art of running in heels [large type] - Gibson, Rachel (Gibson, Rachel. Chinooks Hockey Team, 2018)
"Lexie Kowalsky, a runaway bride from a reality TV show, hops a float plane for Sandspit, British Columbia. Sharing her flight is Sean Knox, new star of the Seattle Chinooks, the hockey team her father coaches. Sean knows this could spell trouble for his career, but the chemistry is too strong to ignore"--